PENGARUH IKLAN DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SITUS BELANJA ONLINE LAZADA (STUDI KASUS PADA MAHASISWA SEMESTER VI PROGRAM STUDI SARJANA MANAJEMEN STIE SULTAN AGUNG) - Selly, Selly; Lie, Darwin; Efendi, Efendi; Nainggolan, Nana Triapnita (SULTANIST: Jurnal Manajemen dan Keuangan, 2019)
The purpose of this research is: 1. To determine the description of advertising, sales promotion of purchasing consumer decisions online shopping Lazada (study case on the college student for management program bachelor semester 6th). 2. To determine the influence of advertising and sales promotion of the purchasing costumer decision online shopping Lazada (study case on the college student for management program bachelor semester 6th at STIE Sultan Agung).The result of this study can be summarized a follows: 1. Ads are good, sales promotion are high and the decision is good. 2. The result of multiple linear regression analysis show that there is a positive influence between advertising and sales promotion on purchasing consumer decision. 3. The result of the analysis of the correlation coefficients obtain are high and positive relationship between advertising and sales promotion to consumer purchasing decision. Then viewed from the coefficient of determination shows whether or not a consumer purchase decision can be explained by advertising and sales promotion while the rest is influenced by other variables.4. Hypothesis test result stated Ho rejected means advertising and sales promotion have a positive and significant impact on purchasing consumer decisions both simultaneously and partially.Â Keyword: Advertisement, Sales Promotion and Purchasing Consumer Decision